Stimulation of Interest in Saving and Investing in the Capital Market - Ade, Sinar Hubriyan; Tamrin, Moh.; Wibowo, Bagus Yunianto; Amalia, Evinta (PT FORMOSA CENDEKIA GLOBAL, 2024)
Saving is a wise and strategic step that illustrates a person's commitment to financial well-being and security in the future. This service was carried out in the community of Sukorejo Village, Gunungpati District, Semarang City. This socialization needs to be carried out so that participants can prepare for retirement which can provide financial freedom in old age. The goal to be achieved is to provide understanding to the public about the importance of saving and investing. This activity applies presentation and question and answer methods. The service team provided supporting materials in the form of brochures and booklets that could be a reference for participants. This service aims to stimulate people's interest in saving and investing and create a more financially independent society as well as prepare for emergencies and a better retirement.